Post-Partum Skin-to-Skin Care and Infant Safety: Results of a State-Wide Hospital Survey. (January 2021) - Tyrala, Eileen; Goodstein, Michael H.; Batra, Erich; Kelly, Barbara; Bannon, Judy; Bell, Ted
Objectives . Survey current experience with Skin to Skin care (SSC) in Pennsylvania Maternity Centers. Study Design . The nursing director of each Maternity Center in PA (n = 95) was sent an on-line confidential survey querying SSC practices. Responses were compared by delivery size, location, and nature of affiliation. Statistics analyzed by chi-square and student t-test. Results. Of these 64/95 MCs (67%) responded. All allowed SSC after vaginal deliveries, 55% after C-section, 73% mother's room. Monitoring included delivery room nurse (94%) with support from other providers (61%), family members (37%), and electronic monitoring (5%). If SSC occurred in mother's room all reported family education on safe practices. 40% were aware of adverse SSC events, including falls and suffocation. About 80% educated staff about infant safety during SSC. Conclusions. Gaps in education and supervision during SSC were identified. Additional education and standardization of best practices are needed to reduce risks from falls and suffocation during SSC.